IMPROVING PATIENT SAFETY USING TECHNOLOGY: A CASE STUDY - Cicero da Silva, Luciano; Pantaleão da Silva, Cristiano; Eduardo da Silva, Rogério (Revista Gênero e Interdisciplinaridade, 2023)
The patient safety culture has historically contributed to the avoidance of adverse events in healthcare organizations. With this, it has become essential that professionals be involved in risk management strategies. This article aims to present a case study of a hospital in the city of Franca/SP, where a set of strategies focused on patient identification was developed. A set of strategies was carried out with the support of technology. The result was a decrease in errors in the assistance process.